2001
DOI: 10.1523/jneurosci.21-01-00010.2001
|View full text |Cite
|
Sign up to set email alerts
|

The Cerebellum-Specific Munc13 Isoform Munc13-3 Regulates Cerebellar Synaptic Transmission and Motor Learning in Mice

Abstract: Munc13 proteins form a family of three, primarily brain-specific phorbol ester receptors (Munc13-1/2/3) in mammals. Munc13-1 is a component of presynaptic active zones in which it acts as an essential synaptic vesicle priming protein. In contrast to Munc13-1, which is present in most neurons throughout the rat and mouse CNS, Munc13-3 is almost exclusively expressed in the cerebellum. Munc13-3 mRNA is present in granule and Purkinje cells but absent from glia cells. Munc13-3 protein is localized to the synaptic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
113
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(125 citation statements)
references
References 29 publications
12
113
0
Order By: Relevance
“…However, we observed a sevenfold difference in their absolute inhibitory strengths (BC 3 PC, 1.73 Ϯ 0.55 nA; SC 3 PC, 0.24 Ϯ 0.04 nA), which would be mostly attributable to the different size of the presynaptic terminals (Palay and ChanPalay, 1974). Munc13-3 KO mice did not change the depression time course at the BC 3 PC synapse (n ϭ 3; data not shown), confirming that Munc13-3 was not involved in inhibitory synaptic transmission (Augustin et al, 2001). …”
Section: Inhibitory Synapses Are Depressingmentioning
confidence: 65%
See 1 more Smart Citation
“…However, we observed a sevenfold difference in their absolute inhibitory strengths (BC 3 PC, 1.73 Ϯ 0.55 nA; SC 3 PC, 0.24 Ϯ 0.04 nA), which would be mostly attributable to the different size of the presynaptic terminals (Palay and ChanPalay, 1974). Munc13-3 KO mice did not change the depression time course at the BC 3 PC synapse (n ϭ 3; data not shown), confirming that Munc13-3 was not involved in inhibitory synaptic transmission (Augustin et al, 2001). …”
Section: Inhibitory Synapses Are Depressingmentioning
confidence: 65%
“…To gain additional insights of the difference between GC 3 BC and GC 3 SC synapses, we studied knockout (KO) mice of Munc13-3, a presynaptic protein implicated in synaptic vesicle priming (Augustin et al, 1999;Basu et al, 2007). Deletion of Munc13-3, a cerebellar-specific isoform of Munc13 (Augustin et al, 2001), has been shown to induce an increase of paired-pulse facilitation in granule cell 3 Golgi cell synapses (Beierlein et al, 2007). We observed an increase of the pairedpulse facilitation also in GC 3 BC synapse ( Fig.…”
Section: Feedforward Inhibition Circuits Activated By Granule Cell Stmentioning
confidence: 99%
“…While channelopathies often follow a dominant mode of inheritance (Koch et al 1993), recessive modes have been seen as well (Trip et al 2008), and several channel proteins are known to underlie severe seizure disorders, such as KCNQ2 (Ohtahara syndrome) (Yamatogi and Ohtahara 2002) and paralogs of SCN4A, such as SCN1A (Wolff et al 2006), SCN2A (Kearney et al 2001), and SCN9A (Singh et al 2009). In addition, the child has compound heterozygous missense mutations in UNC13C, a gene known to result in an inability to learn complex motor tasks in mouse knockouts (Augustin et al 2001).…”
Section: Identifying Plausibly Pathogenic Genetic Variation In the Ddmentioning
confidence: 99%
“…For the knockdown of rat Munc13-1, the target sequences 5′-GCGGC TGAGAAGAGTTCTA-3′ (KD1) and 5′-GCAAC AAGCCTGAGATCTT-3′ (KD2) were obtained using Invitrogen BLOCK-iT RNAi designer (http:// The Munc13 family comprises the following five proteins: Munc13-1, bMunc13-2, and Munc13-3, which were originally identified as neuronal isoforms, uMunc13-2, which was identified as a ubiquitously expressed splicing variant of bMunc13-2, and Munc13-4, which was identified as a non-neuronal isoform (20). Munc13-1, u/bMunc13-2, and Munc13-3 are involved in neurotransmitter release as expected (2,3,23,32); however, Munc13-1 is also required for insulin secretion in pancreatic β cells (21). On the other hand, Munc13-4 is involved in regulated exocytosis in hematopoietic secretory cells, such as cytotoxic T lymphocytes (CTLs), platelets, neutrophils, and mast cells (7,12,27,30,33,35).…”
Section: Rt-pcr and Quantitative Real-time Rt-pcrmentioning
confidence: 99%